2015
DOI: 10.1074/jbc.m115.673988
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hyperinsulinemia Causes Selective Insulin Resistance and Down-regulates Uncoupling Protein 3 (UCP3) through the Activation of Sterol Regulatory Element-binding Protein (SREBP)-1 Transcription Factor in the Mouse Heart

Abstract: The risk for heart failure and death after myocardial infarction is abnormally high in diabetic subjects. We and others have shown previously that mitochondrial uncoupling protein 3 (UCP3) improves functional recovery of the rodent heart during reperfusion. Here, we demonstrate that pharmacological induction of hyperinsulinemia in mice down-regulates myocardial UCP3. Decreased UCP3 expression was linked to the development of selective insulin resistance in the heart, characterized by decreased basal activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…Inconsistent with the present finding, both T 3 and T 2 upregulated skeletal muscle UCP-3 in hypothyroid rat models (Lanni et al 1999;de Lange et al 2001). Hyperinsulinemia is known to suppress the skeletal muscle UCP-3 (Harmancey et al 2015). Additionally, SIRT-1 can repress the glucocorticoid induced UCP-3 gene expression in skeletal muscle (Amat et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Inconsistent with the present finding, both T 3 and T 2 upregulated skeletal muscle UCP-3 in hypothyroid rat models (Lanni et al 1999;de Lange et al 2001). Hyperinsulinemia is known to suppress the skeletal muscle UCP-3 (Harmancey et al 2015). Additionally, SIRT-1 can repress the glucocorticoid induced UCP-3 gene expression in skeletal muscle (Amat et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, expression of constitutive active PI3K and Akt in cardiomyocytes compromises the insulin-induced GLUT4-dependent glucose uptake [13]. Abnormal insulin signaling plays an essential role in the development of HF, including cardiac cell survival, hypertrophy, and fibrosis [14]. In the late stage of HF, IR develops in both cardiac and peripheral tissues such as skeletal muscle, fat, and liver [15], and presents a poor prognosis of HF associated with worsening cardiac function and increasing mortality.…”
Section: Sympathetic Nervous Activity and Insulin Resistance In Heartmentioning
confidence: 99%
“…Regulation of myocardial UCP3 with hyperinsulinemia and type 2 diabetes is less clear with reports of either unchanged [ 12 , 34 ], increased [ 51 ], or decreased expression [ 11 , 32 , 33 ], in the rodent models explored so far. In mice, we previously demonstrated that chronic hyperinsulinemia down-regulates myocardial UCP3 content by 40% through induction of pathway-selective insulin resistance, increased recruitment of the sterol regulatory element-binding protein (SREBP)-1 transcription factor at the UCP3 promoter, and transcriptional repression of the UCP3 gene [ 31 ]. In rats rendered insulin resistant by high-sucrose feeding, we observed a similar decrease in cardiac UCP3 levels that was associated with decreased rates of myocardial LCFA oxidation after ischemia and impaired recovery of contractile function [ 33 ].…”
Section: Introductionmentioning
confidence: 99%